2011
DOI: 10.4236/wjv.2011.13009
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Family Physicians Regarding Adult Vaccination

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…However, about one fourth of participants think that there is no need to establish antibody levels before hepatitis B vaccination and another one fourth of them think that their knowledge about adult vaccination is insufficient. These findings are in accordance with those of Baykan et al, 11 in Turkey, who found that 83% of primary Findings of the present study showed that most primary health care physicians had poor practice regarding adult vaccination, while only 10% had good practice. About three fourths of primary health care physicians received influenza and hepatitis B vaccines, while 40.8% received tetanus vaccine, 21.4% received the pneumococcal vaccine and 13.6% received the HPV vaccine.…”
Section: Data Collection Toolsupporting
confidence: 93%
See 4 more Smart Citations
“…However, about one fourth of participants think that there is no need to establish antibody levels before hepatitis B vaccination and another one fourth of them think that their knowledge about adult vaccination is insufficient. These findings are in accordance with those of Baykan et al, 11 in Turkey, who found that 83% of primary Findings of the present study showed that most primary health care physicians had poor practice regarding adult vaccination, while only 10% had good practice. About three fourths of primary health care physicians received influenza and hepatitis B vaccines, while 40.8% received tetanus vaccine, 21.4% received the pneumococcal vaccine and 13.6% received the HPV vaccine.…”
Section: Data Collection Toolsupporting
confidence: 93%
“…Vaccination against influenza was received by most participant primary care physicians in the present study (75.7%). Lower rates have been reported by Baykan et al, [11] in Turkey (58.5%). Moreover, vaccination rates of physicians' first degree relatives were also low.…”
Section: Data Collection Toolmentioning
confidence: 53%
See 3 more Smart Citations